Navigating The 'fluid' Scholarly Publishing Environment For African Academics - Motaung, Thabiso (My University, 2023)
In the dynamic landscape of scholarly dissemination, the traditional models of academic publishing have been subject to substantive change. However, this has often been met with several challenges including resource constraints, language diversity, historical disparities, and infrastructure gaps. These challenges can slow down academic progress and are especially pronounced on the African continent. To navigate such a fluid environment strategically, academics on this continent must enhance the visibility and impact of their research in order to achieve global recognition to attract more international collaborations and research funding, as well as to facilitate knowledge exchange, collaboration, and access to resources. Here, we explore the impact of a fluid nature of scholarly publishing on the continent and provide an overview of how researchers in Africa may navigate this dynamic environment. We explore mechanisms for enhancing the visibility, quantity and impact of African research.
Keywords: African Academics; Scholarly Publishing Environment; African Research